2010
DOI: 10.1017/s0031182010000351
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism underground: determinants of helminth infections in two species of subterranean rodents (Octodontidae)

Abstract: Patterns of infection among hosts in a population are often driven by intrinsic host features such as age or sex, as well as by positive or negative interactions between parasite species. We investigated helminth parasitism in 2 South American rodent species, Ctenomys australis and C. talarum (Octodontidae), to determine whether the unusual solitary and subterranean nature of these hosts would impact their patterns of infection. We applied generalized linear models to infection data on a total of 7 helminth sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
(52 reference statements)
5
28
0
1
Order By: Relevance
“…The low number of species found does appear to be a typical pattern for mole-rats based on previous studies that have investigated the ectoparasites of bathyergids (De Graaff, 1964, 1981Viljoen et al, 2011). This impoverished endoparasite fauna may be a result of limited parasite exposure in the subterranean habitat of such rodents (Rossin et al, 2010;Viljoen et al, 2011). We cannot exclude the possibility that our sampling approach might have missed additional ectoparasites and that the lack of ticks encountered in this study is partially attributable to animals being sampled several days after capture.…”
Section: Discussionmentioning
confidence: 77%
“…The low number of species found does appear to be a typical pattern for mole-rats based on previous studies that have investigated the ectoparasites of bathyergids (De Graaff, 1964, 1981Viljoen et al, 2011). This impoverished endoparasite fauna may be a result of limited parasite exposure in the subterranean habitat of such rodents (Rossin et al, 2010;Viljoen et al, 2011). We cannot exclude the possibility that our sampling approach might have missed additional ectoparasites and that the lack of ticks encountered in this study is partially attributable to animals being sampled several days after capture.…”
Section: Discussionmentioning
confidence: 77%
“…Specifically, by contrasting new information from a 2nd population (NC) of C. talarum with data obtained previously for animals at MdC (Cutrera et al 2011(Cutrera et al , 2012, we use the pronounced differences in parasite load between these populations to assess how spatial variation in this attribute influences immunogenetic variation and selection on MHC genes in this species. Gastrointestinal parasite load in C. talarum at NC is markedly lower than at MdC (Rossin and Malizia 2002;Rossin et al 2010). Assuming that increased intensity of parasite infection is associated with enhanced parasite-mediated selection on MHC (reviewed by Charbonnel et al 2006), we predict that MHC-DRB diversity and evidence of selection upon this locus will be lower, the correlations between matrices of MHC genotypes and those of parasite load or immunocompetence will be weaker, allele divergence will be smaller, and use of MHC-associated cues in mate choice will be less apparent in NC compared to previous findings in MdC.…”
mentioning
confidence: 93%
“…Long-term studies in 2 populations of the Talas tuco-tuco (C. talarum) from southeastern Argentina have reported marked differences with respect to several demographic characteristics, including animal density and adult sex ratio (Busch et al 1989;Malizia et al 1991), degree of polygyny and kin structure (Zenuto et al 1999a(Zenuto et al , 1999bCutrera et al 2005), and effective population size ). In particular, comparative studies of these 2 demographically distinct populations have demonstrated that number of alleles, heterozygosity, and estimated intensity of selection at 2 class II loci (DRB and DQA) are greater in the population characterized by higher density (Mar de Cobo [MdC]: mean number of individuals/ha 6 SD: 57 6 6; Necochea [NC]: 15 6 4 individuals/ha-see Busch et al 1989;Malizia et al 1991;) and greater parasite exposure (greater parasite prevalence [the percentage of infected individuals in the population], richness, and intensity of infection- Rossin and Malizia 2002;Rossin et al 2010), as expected if parasite-driven selection maintains MHC polymorphism in this species . Detailed analyses of 1 of these populations (MdC) have revealed that specific DRB alleles are associated with parasite load and intensity of humoral immune response (Cutrera et al 2011), suggesting that individual MHC sequences influence resistance to pathogens.…”
mentioning
confidence: 99%
“…In subterranean hosts, the restrictions of the environment appear to impact on how parasite infections are spread due to limitations on host dispersal (Hafner et al, 2000;Rossin et al, 2010;Archer et al, 2016). Most studies on the parasite fauna of subterranean rodents indicate that parasite diversity is low as a consequence of the restrictive environment of the burrow (Hafner et al, 2000;Rossin and Malizia, 2002;Rossin et al, 2010;Lutermann and Bennett, 2012;Lutermann et al, 2015).…”
mentioning
confidence: 99%
“…was greater in the dry season despite greater prevalence in the wet season does not seem to support this hypothesis. Energetic constraints due to increased restrictions on foraging as well as higher reinfection rates within a colony as a result of smaller home ranges in the dry season may increase both host susceptibility and exposure to this worm and this could account for the observed pattern (Rossin et al, 2010;Viljoen et al, 2011).…”
mentioning
confidence: 99%